Pengaruh Suhu Penyimpanan terhadap Kadar Gula pada Berbagai Bagian Umbi Bawang Bombay - Suharwadji Sentana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
Onion is usually stored at either low (± 0ºC) or high (± 30ºC) temperature at 60%-75% relative humidities. Storage at high temperatures, however, results in loss of pyruvic acid and ascorbic acid, while low temperature storage, makes onion tends to develop brown colour brown colour during dehydration. This experiment was designed to find out the effect of storage temperature on the change of sugar levels of various parts of onion bulbs. Southport White Globe onions were stored at 0ºC and 30ºC at 60% relative humidity for 20 weeks; fructose, glucose, and sucrose contents of top, middle, and bottom part of onion bulbs were monthly investigated by Gorin method. The results show that fructose, glucose, and sucrose contents at the top, middle, and bottol bulb parts during storage had the same pattern of change, they increased at the beginning and then decreased at the enf of storage. At the week 12, sucrose levels in all different bulb parts stored at 0ºC increased sharply compared to those stored at 30ºC and then declined towards the end of storage.